2019
DOI: 10.1007/s00373-019-02032-3
|View full text |Cite
|
Sign up to set email alerts
|

On the Integrability of Strongly Regular Graphs

Abstract: Koolen et al. showed that if a connected graph with smallest eigenvalue at least −3 has large minimal valency, then it is 2-integrable. In this paper, we will prove that a lower bound for the minimal valency is 166.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…(ii) It is known that κ 1 is at least 166 by results of Koolen and Munemasa [59] and Koolen, Rehman and Yang [61].…”
Section: ]mentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) It is known that κ 1 is at least 166 by results of Koolen and Munemasa [59] and Koolen, Rehman and Yang [61].…”
Section: ]mentioning
confidence: 99%
“…At the end of this survey, we give some problems for discussion. In [61], Koolen et al showed that the complement of the McLaughlin graph has smallest eigenvalue −3 and can not be 2-integrated, but it is 4-integrable. It is not clear whether any graph with smallest eigenvalue at least −3 is always 4-integrable.…”
Section: Future Workmentioning
confidence: 99%
“…Note that M cL is the unique strongly regular graph with parameters (275, 162, 105, 81), as the McLaughlin graph is uniquely determined by its parameters (See [6]). In [11], Koolen et al showed that M cL is not 2-integrable. Let H be the 3-point cone over M cL, that is, H is obtained by adding 3 new vertices to M cL and joining these three vertices to all the vertices in M cL and to each other.…”
Section: Introductionmentioning
confidence: 99%